Stochastic Optimal Power Flow of Wind Turbine through Flexible Grid Connected System Considering Converter Loss - Jiahui DU; Changjiang WANG; Ling LI; Chenguang YANG (Zhongguo dianli)
Because of the randomness and volatility of wind power, large-scale grid-connection will bring great challenges to the safe and stable operation of power systems. Therefore, it is necessary to deeply study the stochastic optimal power flow of wind power through (VSC-HVDC) grid-connection system. In this paper, a stochastic optimal power flow model for wind power through flexible DC grid-connected system is presented, which takes into account converter loss and wind power randomness. Firstly, the mathematical model of wind power and the VSC-HVDC mathematical model considering converter loss are established, and different control methods of the converter stations are analyzed when wind power is grid-connected. Secondly, scenario method is used to simulate the uncertainty of wind power, and Kantorovich distance based scenario cutting technology is used to improve the calculation efficiency. Thirdly, the stochastic optimal power flow model of wind power through the flexible DC grid-connected system is constructed, and the model is solved by the interior point method, and the numerical characteristics of output variables are obtained by using the statistical method. Finally, taking the modified WECC 2 machine 5 node and IEEE-118 node system as examples, the calculation example is analyzed to verify the rationality and validity of the proposed optimal model.